Penguatan Karakter Kinerja Kepemimpinan Siswa SMA Negeri I Pariangan Kabupaten Tanah Datar - Ismira, Ismira (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2022)
This article was written as a reflection of the community service activities of Adzkia University lecturers. This service is carried out in the context of basic level leadership training activities for the OSIS team (Intra-School Student Organization) and class leaders at Senior High School Pariangan District, Tanah Datar Regency, West Sumatra Province, Indonesia. The topic presented was entitled "Development of Minangkabau Culture-Based Performance Character for Independence". After that, we distributed inventories to measure the quality of student leadership performance. The research method uses descriptive quantitative methods. Research inventories measure aspects of knowledge, attitudes and skills. The knowledge aspect measures the character of critical and creative performance. The attitude aspect measures of individual attitudes, social attitudes and spiritual attitudes. The skill aspect measures of communication skills, collaboration skills and digital skills. The results showed that the leadership performance of SMA Negeri 1 Pariangan students were in the "good quality" criteria. The performance character with the highest quality is found in the religious attitude performance character with the Respondent's Achievement Level of 95.66%. The critical performance character gets the lowest score but is still in the "good quality" category with the Respondent's Achievement Level of 78.19%. The measurement results explain that the leadership performance character student of Senior High School Pariangan District, Tanah Datar Regency, West Sumatra Province, Indonesia is "good quality".